100% renewable energy in Japan. (1st March 2022) - Cheng, Cheng; Blakers, Andrew; Stocks, Matthew; Lu, Bin
Highlights: Japan can be self-sufficient for electricity supply at competitive costs. Sufficient renewable energy resources in Japan to achieve carbon neutrality. Geographic Information System based renewable resource assessment. 40-year hourly energy balance analysis to find the least-cost system configuration. A wide range of scenarios yield costs in the range of US86–110/Megawatt-hour. Abstract: Low-cost solar photovoltaics and wind offer a reliable and affordable pathway to deep decarbonization of energy, which accounts for three quarters of global emissions. However, large-scale deployment of solar photovoltaics and wind requires space and may be challenging for countries with dense population and high per capita energy consumption. This study investigates the future role of renewable energy in Japan as a case study. A 40-year hourly energy balance model is presented of a hypothetical 100% renewable Japanese electricity system using representative demand data and historical meteorological data. Pumped hydro energy storage, high voltage interconnection and dispatchable capacity (existing hydro and biomass and hydrogen energy produced from curtailed electricity) are included to balance variable generation and demand. Differential evolution is used to find the least-cost solution under various constraints. This study shows that Japan has 14 times more solar and offshore wind resources than needed to supply 100% renewable electricity and vast capacity for off-river pumped hydro energy storage. Assuming significant cost reductions of solar photovoltaics and offshore wind towards global norms in the coming decades driven by large-scale deployment locally and global convergence of renewable generation costs, the levelized cost of electricity is found to be US86/Megawatt-hour for a solar-dominated system, and US110/Megawatt-hour for a wind-dominated system. These costs can be compared with 2020 average system prices on the spot market in Japan of US102/Megawatt-hour. Cost of balancing 100% renewable electricity in Japan ranges between US20–27/Megawatt-hour for a range of scenarios. In summary, Japan can be self-sufficient for electricity supply at competitive costs, provided that the barriers to the mass deployment of solar photovoltaics and offshore wind in Japan are overcome.